Case Report: Dengue Hemorrhagic Fever - Evy Eryta; Muhamad Yoga Rizki Danil; Yulia Nugraha Karsita (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Dengue haemorrhagic fever (DHF) is an infectious disease caused by dengue virus with clinical manifestations of fever, muscle and/or joint pain accompanied by leukopenia, rash, lymphadenopathy, thrombocytopenia and hemorrhagic diathesis. In DHF, plasma permeation is characterized by hemoconcentration (increased hematocrit) or fluid accumulation in body cavities. A case report of a 28-year-old patient came to Dr. Suhatman Hospital, MARS with complaints of continuous fever, accompanied by headache and retro orbital pain and pain in the joints. On physical examination, blood pressure was 130/90 mmHg, temperature 38.5° degree C, flushing (+), tourniquet (+), blood test was obtained. In the supporting examination, routine blood laboratory results obtained thrombocytopenia and leukocytopenia.